Politics and nursing - Susan E van Niekerk (AOSIS, 2001)
Politics implies the art of influencing people, and nurses have the political responsibility to influence the allocation of scarce resources. Opsomming Politiek impliseer die "kuns om besluite te beinvloed" en verpleegkundiges het die politieke verantwoordelikheid om die allokasie van skaars Gesondheidshulpbronne te beinvloed. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.